2019
DOI: 10.1182/bloodadvances.2019000731
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell mutations can be detected in myeloma patients years before onset of secondary leukemias

Abstract: Key Points Leukemia-associated mutations can be detected many years before the onset of secondary leukemias in myeloma patients. Stem and progenitor cells can act as reservoirs of mutations before the onset of secondary MDS and AML after treatment of myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…The same mechanism was recently demonstrated in a cohort of MM patients, years before the evolution to t-MN [115]. In these cases, the presence of pre-existing mutant HSC clones was revealed, mainly harboring TP53 mutations, that became the dominant population at the time of t-MN evolution [115]. This mechanism could explain the high frequency of TP53 mutations in these patients.…”
Section: Therapy-related Mdssupporting
confidence: 70%
See 1 more Smart Citation
“…The same mechanism was recently demonstrated in a cohort of MM patients, years before the evolution to t-MN [115]. In these cases, the presence of pre-existing mutant HSC clones was revealed, mainly harboring TP53 mutations, that became the dominant population at the time of t-MN evolution [115]. This mechanism could explain the high frequency of TP53 mutations in these patients.…”
Section: Therapy-related Mdssupporting
confidence: 70%
“…However, it was shown that the same TP53 mutant clones found at diagnosis had been detected at low frequencies (<1%), 3-6 years before the development of t-MN and even prior to any chemotherapy treatment, supporting the conclusion that t-MN is related to the cytotoxic selection of pre-existing chemo-resistant clones preferentially expanded after treatment [114]. The same mechanism was recently demonstrated in a cohort of MM patients, years before the evolution to t-MN [115]. In these cases, the presence of pre-existing mutant HSC clones was revealed, mainly harboring TP53 mutations, that became the dominant population at the time of t-MN evolution [115].…”
Section: Therapy-related Mdssupporting
confidence: 69%
“…A comprehensive characterization of the genomic changes, and its correlation with the resultant morphological changes, may help identify patients at the risk of imminent leukemic transformation and devise effective preventive strategies. Hence, the identification of individuals at high-risk of developing t-MN and employment of preventative approaches may improvement outcomes for this difficult-to-treat group of patients [ 16 , 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various agents have been developed as drugs able to target CD123 on malignant leukemic cells ( 52 ). In patients with MM who developed AML/Myelodysplastic Syndromes, stem, and progenitor cells (collected years before the onset of secondary disease) expressed high CD123 levels ( 53 ). Here we reported that the expression of CD123 was higher on MM-EV-treated HSCs compared to untreated ones.…”
Section: Discussionmentioning
confidence: 99%